2011
DOI: 10.1002/jor.21545
|View full text |Cite
|
Sign up to set email alerts
|

Knee biomechanics early after knee replacement surgery predict abnormal gait patterns 12 months postoperatively

Abstract: An abnormal flexor moment pattern is often evident following total knee replacement (TKR) surgery. We investigated whether such a pattern at 12 months post-surgery could be predicted using biomechanical gait measures assessed before surgery and at 4 months post-surgery. Thirty two TKR patients were evaluated and classified as normal (biphasic pattern) or abnormal (flexor moment pattern) at each time point. Biomechanical parameters collected before surgery and at 4 months post-surgery were then explored for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…31, details in supplementary material). To assess intra-assessor repeatability, identification of all landmarks was repeated three times on the same 10 subjects (20 limbs).…”
Section: Methodsmentioning
confidence: 99%
“…31, details in supplementary material). To assess intra-assessor repeatability, identification of all landmarks was repeated three times on the same 10 subjects (20 limbs).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has identified distinct walking gait patterns in knee OA patients 10,11 . However, whether also joint loading indices (KAM, KAM impulse, static alignment) vary among these gait patterns, has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…They found that TKA produced no change in static foot posture but did significantly alter hindfoot kinematics during gait. In that same year, they investigated whether biomechanical gait variables assessed before and at 4 months after surgery could predict an abnormal flexor moment pattern at 12 months after surgery. Interventions aimed at improving active extension may need to be implemented as early as possible after surgery to restore to a normal gait pattern and their data may help in achieving that goal.…”
Section: Introductionmentioning
confidence: 99%